A critical assessment of the Candida strains isolated from cigar tobacco leaves - Jia, Yun; Zhou, Wen; Yang, Zhen; Zhou, Quanwei; Wang, Yue; Liu, Yi; Jia, Yuhong; Li, Dongliang (Frontiers in Bioengineering and Biotechnology, 2023)
[Introduction] Candida genus plays a crucial role in cigar fermentation, and strains from different sources might have differences in metabolic characteristics. Therefore, this study conducted directional isolation of Candida strains from cigar tobacco leaves and compared their fermentabilities to screen suitable strains for cigar fermentation, thereby improving the cigar quality. [Methods] First, the Candida strains from cigars tobacco leaves in different production areas were directionally isolated by pure culture. Then, the isolated strains were screened based on chemical indexes and flavor component contents. Finally, the fermentabilities of preferred strains were verified by sensory evaluation. [Results] Five strains of C. parapsilosis and four strains of C. metapsilosis were obtained through directional isolation. By comparing the physicochemical indexes of nine strains of Candida, it was found that C. parapsilosis P1 and C. metapsilosis M4 not only reduced the alkaloids content (by 25.3% and 32.6%, respectively) but also increased the flavor components content (by 25.2% and 18.9%, respectively). Among them, P1 could raise the content of chlorophyll degradation products, carotenoid degradation products, and Maillard reaction products, and enhance the beany and nutty flavor of cigars. M4 could raise the content of chlorophyll degradation products, cembranoids degradation products, and Maillard reaction products, and improve the baking, nutty, cocoa, and honey flavor of the cigar. [Discussion] In this study, the Candida strains were directionally isolated from cigars tobacco leaves in different production areas, and two functional strains suitable for cigar fermentation were screened based on physicochemical indexes and sensory evaluation, which would contribute to the directed regulation of cigar quality and flavor diversification.